Epidemiological Analysis of Diphtheria Cases in Hodeida, Yemen: A Review of Admission Records from 2018 to 2022 - Moulhee, Najeeb Mohammed Saed; Alwesabi, Sadeq Abdo Mohammed; Taha, Mogeeb Saeed; Majam, Ahmed Suliman Mohamed (Journal of medical and pharmaceutical sciences, 2025)
Diphtheria is a potentially fatal infectious disease caused by Corynebacterium diphtheriae, a non-encapsulated, gram-positive bacillus. The disease is primarily transmitted through close respiratory contact, leading to nasopharyngeal infections that may cause airway obstruction and, in severe cases, systemic involvement. Yemen had not previously experienced large-scale outbreaks until a major epidemic emerged between October 2017 and August 2018, during which 2,203 suspected cases were reported, resulting in 116 deaths. Objective: to conduct an epidemiological analysis of diphtheria cases in Hodeida, Yemen. Methodology: The study design was a descriptive, retrospective, cross-sectional hospital-based study. The sample size comprised the total number of diphtheria patients who attended Al-Thawra General Hospital in Hodeidah Governorate, Yemen, during the study period from 2018 to 2022; where their number reached 534 cases. Results: the results indicated that the prevalence of diphtheria in Hodeida governorate was 534 cases. The highest prevalence was in Al-Hawk District, with 129 cases, or 24% of the cases, followed by Al-Hali District, with 106 cases, or 19.8%. The study results showed that (63%) of the participants infected with diphtheria were females, while (37%) were males. The children aged 10 years and under were the most affected during this diphtheria outbreak (46.54%), compared to those in the older age group 11-20, which was 29.16% as well. The prevalence of diphtheria was highest among those with incomplete vaccination (7.9 %). Conclusion: the study found a significant increase in the prevalence of diphtheria in Hodeida governorate. As well as showing that incomplete vaccinations are associated with higher rates of several complications.